Effects of thermal oxidising exposure on the tensile strength of Hi-Nicalon fibres. (19th May 2018) - Wu, Shoujun; Cheng, Laifei
ABSTRACT: Hi-Nicalon TM silicon carbide fibre tows were respectively exposed to argon, pure oxygen, and wet oxygen atmosphere at 1300–1500 °C for 1 h. The tensile strength of the Hi-Nicalon fibres decreased dramatically with increasing temperature under all exposure conditions. The most severe deterioration of the tensile strength of the fibres, which occurred under exposure to pure oxygen, because of the synergistic effects of microcracking of silica formed by oxidation and the growth of SiC-nanocrystals at high temperature. The relatively high effective load-bearing area and uniform loading resulting from rapid formation of viscous silica under the wet oxygen environments were considered as reasons for the intermediate deterioration of the tensile strength of the fibres.